Assembly of SnSe Nanoparticles Confined in Graphene for Enhanced Sodium‐Ion Storage Performance. Issue 4 (17th December 2015) - Yang, Xu; Zhang, Rongyu; Chen, Nan; Meng, Xing; Yang, Peilei; Wang, Chunzhong; Zhang, Yaoqing; Wei, Yingjin; Chen, Gang; Du, Fei
Abstract: Sodium‐ion batteries (SIBs) have attracted much interest as a low‐cost and environmentally benign energy storage system, but more attention is justifiably required to address the major technical issues relating to the anode materials to deliver high reversible capacity, superior rate capability, and stable cyclability. A SnSe/reduced graphene oxide (RGO) nanocomposite has been prepared by a facile ball‐milling method, and its structural, morphological, and electrochemical properties have been characterized and compared with those of the bare SnSe material. Although the redox behavior of SnSe remains nearly unchanged upon the incorporation of RGO, its electrochemical performance is significantly enhanced, as reflected by a high specific capacity of 590 mA h g −1 at 0.050 A g −1, a rate capability of 260 mA h g −1 at 10 A g −1, and long‐term stability over 120 cycles. This improvement may be attributed to the high electronic conductivity of RGO, which also serves as a matrix to buffer changes in volume and maintain the mechanical integrity of the electrode during (de)sodiation processes. In view of its excellent Na + storage performance, this SnSe/RGO nanocomposite has potential as an anode material for SIBs. Abstract : Nanocomposite anodes : A SnSe/RGO nanocomposite has been prepared by a facile ball‐milling method and its structural, morphological, and electrochemical properties have been studied and compared with those of bare SnSe. The experimental results clearly demonstrate an improvement in the reversible capacity, rate capability, and capacity retention after long‐term cycling (see figure).